2014
DOI: 10.5114/jcb.2014.40767
|View full text |Cite
|
Sign up to set email alerts
|

Multi-catheter interstitial accelerated partial breast irradiation – tips and tricks for a good insertion

Abstract: Adjuvant radiotherapy is recommended post breast conserving surgery. Accelerated Partial Breast Irradiation (APBI) offers a more attractive shorter course of treatment over 5 days compared to standard conventional external beam radiotherapy, which is often protracted. Multi-catheter interstitial APBI offers excellent dosimetric coverage. This article describes two insertion techniques for multi-catheter interstitial APBI, the operator dependent freehand technique, and the easier to learn template technique. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Within 8 weeks of lumpectomy and axillary nodal evaluation, patients underwent an interstitial implant using the template method performed in the supine position. 17 , 18 Once the cavity was localized, the ipsilateral breast area was surgically prepared under sterile conditions. To avoid injuring the underlying chest wall structures or causing a pneumothorax, the overlying breast was pinched and gently lifted off the chest wall before applying the template and securing it.…”
Section: Methodsmentioning
confidence: 99%
“…Within 8 weeks of lumpectomy and axillary nodal evaluation, patients underwent an interstitial implant using the template method performed in the supine position. 17 , 18 Once the cavity was localized, the ipsilateral breast area was surgically prepared under sterile conditions. To avoid injuring the underlying chest wall structures or causing a pneumothorax, the overlying breast was pinched and gently lifted off the chest wall before applying the template and securing it.…”
Section: Methodsmentioning
confidence: 99%
“…However, MIB is the oldest and time tested technique of delivering breast brachytherapy with respect to mature clinical outcome data [ 3 ]. In fact, it is being practiced since almost a decade before the guidelines for APBI were formulated [ 4 , 5 ]. As it is technically demanding and delivered without the need of any expensive device, it is not a very popular technique.…”
Section: Purposementioning
confidence: 99%
“…Initially, CT imaging was used only for evaluation purpose after standard fluoroscopy-guided implantation [ 12 , 13 , 14 , 15 , 29 ], but afterwards, the implantations themselves were performed using 3D CT information [ 15 , 16 , 30 , 31 , 32 , 33 ]. These and other studies confirmed that with introduction of image-guided implantation techniques, the treatment plans improved considerably compared to the traditional fluoroscopy-guided implantation and planning [ 11 , 34 ].…”
Section: Discussionmentioning
confidence: 99%